Implementasi Mengajar Menurut Edwin Ray Guthrie pada Guru PAK - Erlangga Saputra; Sandra Rosiana Tapilaha; Yuslina Halawa; Surimawati Laia (Sepakat : Jurnal Pastoral Kateketik, 2025)
Edwin Ray Guthrie's learning theory, known as the concept of contiguity, emphasizes the importance of a direct relationship between stimulus and response in the learning process. According to this theory, a response tends to be repeated if the same stimulus reappears, thus becoming the main key in forming certain habits or behaviors. In the context of Christian Religious Education (PAK), this theory is relevant to be applied in teaching moral and spiritual values, such as love, honesty, loyalty, and forgiveness. Learning based on fragmentation and conditioning aims to shape the character of students consistently, sustainably, and in a directed manner according to Christian teachings. The main challenge in implementing this theory is maintaining the consistency of the stimulus in a dynamic classroom environment and requiring teachers to act not only as a transmitter of material, but also as a real life role model for students. Therefore, Guthrie's theory needs to be adapted through a more holistic approach, by integrating spiritual reflection, habituation of Christian values, and contextual application. Support for the repetition method is also found in Bible teachings, such as Deuteronomy 6:4-9, which emphasizes the importance of teaching the values ​​of faith continuously and sustainably to the next generation.